The 1997 Howard Street Robinson Lecture: The Mesoproterozoic Nain Plutonic Suite in Eastern Canada, and the Setting of the Voisey's Bay Ni-Cu-Co Sulphide Deposit - Ryan, Bruce (Geoscience Canada, 1997)
Summary Northern Labrador is home to one of the world's classic anorogenic magmatic terranes, the Mesoproterozoic Nain Plutonic Suite (NPS), comprising a broad spectrum of coalesced basic and silicic intrusions emplaced ca. 1.35-1.29 Ga astride a Paleoproterozoic continental suture zone. Tectonic models for the development of the NPS relate it to processes associated with a mantle plume impinging on the base of the crust. The NPS is largely a bimodal igneous terrane, of which the predominant rocks belong to the anorthositic and granitic components. Troctolitic and iron-rich dioritic rocks are subordinate. The Reid Brook intrusion, the oldest-recognized troctolitic pluton within the NPS, hosts a major ore deposit of magmatic Ni-Cu-Co sulphide minerals that was discovered north of Voisey's Bay in 1993. The ore is concentrated in three main settings: in a troctolitic dyke (Discovery Hill and the Western Extension), in a bowl-shaped zone (the Ovoid, largely massive sulphide) resting on gneiss, and at the lower levels of a massive troctolite body (the Eastern Deeps). One model for the geometry and distribution of the Voisey's Bay deposit can be constructed by application of physical and chemical processes that would accompany the ascent and deposition of a sulphide-saturated, mantle-derived silicate magma into a mid- to upper-crustal dilational chamber. The silicate magma may have liberated a separate immiscible sulphide magma because of sulphide saturation promoted by interaction with Paleoproterozoic sulphur-bearing paragneisses at a deeper level, or the sulphide liquid may be totally of juvenile mantle extraction. The origin of the sulphide ore, the complete distribution of the ore, and the three dimensional shape of the hosting troctolitic intrusion are subjects of active study, and no doubt there will be revisions to the present working model. There is also no doubt — when all private sector, government, and aboriginal concerns about the Voisey's Bay mine development are addressed — that the exploitation of this major world-class nickel-copper-cobalt resource will accrue economic benefits to the province of Newfoundland and Labrador, as well as the rest of Canada, for decades to come.